Review Consensus Effects on e-Wom and Consumer Goods e-Purchase Satisfaction: Evidence from Vietnam - CUONG, Pham Hung (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).05, 2020)
The reviews of the consumers who are shopping online is playing very important role in shaping the intentions of the purchase of others. The digital platforms are increasing day by day which are giving the opportunity to the customers to share and express their views, comments and ideas, and at the same time it is establishing a powerful tool of marketing which is known as electronic word of mouth (e-WOM) which has become an important source to collect the details about any product for the consumers. Review consensus gives comprehensiveness to e-WOM. Single or limited reviews fail to give a complete picture to the e-WOM, hence to enable customers to make an appropriate decision multiple number of reviews with similarity among them are required. In the present, study a sample of 328 online customers has been considered through a structured questionnaire designed on five-point interval scale. Mean score and Multiple regression were used to analyze the data. The data analysis has been done with help of SPSS 20.0 (Statistical Package for Social Sciences). Through this study it is found that most of the aspects of review consensus have positive impact on e-WOM and E-Purchase Satisfaction for consumer goods.